The distribution of muscle and bone weight in swamp buffalo (Bubalus bubalis), bos indicus and bos taurus Steers - E. R., Johnson; D. D., Charles; D. A., Baker (Universiti Putra Malaysia Press, 2002)
The muscle weight distribution and bone weight distribution of 15 buffalo (Bubalus bubalis) steers were compared with that of 15 steers from each of three breeds ofcattle, Angus, Hereford and Brahman. For both muscle weight distribution and bone weight distribution, buffaloes showed a "shift" towards the forequarter. This involved the cervical, thoracic and forelimb bones and standard muscle groups 5, 7 and 9. Brahmans showed a similar but less pronounced distribution to that of the buffaloes. The scapula was an exception in the forequarter of the buffaloes. It was lighter relative to the other breeds with clearly enlarged mm. supraspinatus and infraspinatus but a lighter m. subscapularis. It is suggested that these distribution differences reflect the traction history of buffaloes and Brahmans.